The role of angiopoietins and their mediators in symptomatic small bowel angiodysplasia; identifying novel diagnostic and therapeutic targets in chronic anaemia and obscure gastrointestinal bleeding - Holleran, Grainne (Trinity College Dublin. School of Medicine. Discipline of Clinical Medicine, 2021)
Title : The role of angiopoietins and their mediators in symptomatic small bowel angiodysplasia; identifying novel diagnostic and therapeutic targets in chronic anaemia and obscure gastrointestinal bleeding. Author: Dr Grainne Holleran Introduction and aim: Small bowel angiodysplasia (SBA) is a condition characterised by weakened blood vessels in the intestinal mucosa, prone to recurrent, often significant bleeding, often difficult to diagnose, and associated with a reduced quality of life in affected patients. Advancements in diagnostic tools and effective therapies has been limited by a lack of understanding of the pathophysiology behind the condition. The aim of this thesis was to determine the role of various angiogenic factors in the pathophysiology of SBA; to identify specific factors which may be used as diagnostic or prognostic markers, or therapeutic targets, which may improve management options. Methods: 1. Introduction to the condition of SBA and gastrointestinal angiodysplasia in general with a focus on currently available diagnostic and treatment options, and a literature review of the current knowledge of angiogenesis in gastrointestinal angiodysplasia. 2. A putative assessment of the role of angiogenic factors identified by the literature to be involved in angiodysplasia formation. Using ELISA technique, we measured the level of a number of angiogenic factors (Ang 1 & 2, VEGF, PDGF-BB, sEnd, TNF-α, vWF) in the serum of SBA patients and non-bleeding controls. Tissue levels of factors found to be significant in the serum assessment were measured from mucosal biopsy samples of SBA lesions using qPCR and compared to macroscopically normal appearing mucosa in patients and controls. 3. A systematic literature review was performed to determine whether clinical factors are predictive of SBA disease presence, severity or prognosis. Further ELISA measurements of Ang 1&2 were performed in a cohort of 120 patients with obscure gastrointestinal bleeding of various causes to determine whether the differences in serum levels of Ang 1&2 were specific for a diagnosis of SBA, and whether a certain level of either factor could be used in the diagnosis of the condition. 4. A commercially available multiplex assessment of 55 angiogenic factors in the serum of SBA patients compared to controls was performed to determine whether any additional angiogenic factors were likely to be involved in SBA formation. Formal serum ELISA measurements of any factors identified (TIMP1, Endostatin, PDGF-AA) were then performed in SBA patients and controls to determine quantitative measurements. Any factors found to be significantly different between the groups were then measured in the cohort of patients with various causes of obscure gastrointestinal bleeding as above. 5. Tissue levels of each of the factors found to be significantly different in the serum of SBA patients and controls (Ang 1&2, Tie2, TIMP1, Endostatin) were then measured from small bowel mucosal biopsies using qPCR. Immunohistochemistry using commercially available antibodies to Ang 1&2 and Tie2 was perfomed to locate the presence of these factors within small bowel mucosal tissue from patients and controls. Results: Clinical factors are not specific for a diagnosis of SBA in a cohort of patients with small bowel bleeding. Serum levels of a number of angiogenic factors were found to differ significantly between SBA patients and controls with SBA patients having higher levels of Ang-2 and TIMP1, and lower levels of Ang-1, TNF-α, and Endostatin. Tissue from SBA lesions was found to have higher levels of Ang-1&2 and Tie2 but there were no differences in levels of any of the other factors measured. We were unable to accurately quantify or locate levels of any of the factors using immunohistochemistry. Conclusion: Our results have identified the angiopoietin pathway, specifically Ang-1&2, and their receptor Tie2, as a significant angiogenic pathway in the pathophysiology of SBA formation and these factors may be used in the future development of diagnostic and prognostic markers, aswell as offering potential therapeutic targets for the condition.
APPROVED